Case Report: Diagnosis of Mucopolysaccharidosis Type IVA With Compound Heterozygous Galactosamine-6 Sulfatase Variants and Biopsy of Replaced Femoral Heads - Ma, Yiyang; Peng, Hao; Hsiang, Fuchou; Fang, Haoyu; Du, Dajiang; Jiang, Chenyi; Wang, Yehui; Chen, Chun; Zhang, Changqing; Gao, Yun (Frontiers in Pediatrics, 2022)
Introduction Mucopolysaccharidosis Type IVA (MPS IVA) or Morquio A Syndrome, is a rare metabolic disorder caused by compromised galactosamine-6 sulfatase (GALNS) encoded by GALNS gene (NM_000512.5), leading to keratin sulfate (KS) and chondroitin-6-sulfate (C6S) accumulation in various organs. We present a 17-year-old female with progressive bilateral hip pain and radiographic evidence of spondyloepiphyseal dysplasia. Methods Diagnosis of MPS IVA was made based on whole exome sequencing (WES) of blood samples collected from the patient and family members, high urinary GAG excretion, supportive clinical manifestations, radiographic examinations including whole-body X-rays, cervical MRI and pelvic CT. Patient underwent bilateral total hip arthroplasties (THAs) sequentially, with a one-month interval. Femoral heads were preserved for micro-CT (μCT) analysis and osteochondral histology examination. Results Patient presented with multiple skeletal deformities, including vertebras and long bone deformities. WES disclosed compound heterozygous variants at exon 11 (c.1156C>T) and exon 12 (c.1288C>G) of the GALNS (NM_000512.5). μCT analysis revealed significant bone quantity loss and microarchitectural change in both weight-bearing area (WBA) and non-weight-bearing area (NWBA) of the femoral heads, while histological analysis showed structural abnormity of articular cartilage in the WBA of the femoral heads. Conclusion We have found compound heterozygous variants of GALNS. This is also the first study to report the microarchitectural and histological changes of both subchondral bone and articular cartilage of femoral head in a MPS IVA patient.